ANALISIS RISIKO USAHATANI KEDELAI DI KECAMATAN RAMAN UTARA KABUPATEN LAMPUNG TIMUR - Tri Naftaliasari; Zainal Abidin; Umi Kalsum (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
This research aims to assess: the profit of soybean farming, the amount of risk faced by soybean farmer, the correlation between risk and profit accepted by the farmers, the sources of risk on soybean farming, and farmer’s effort in handling risk impact on soybean farming. The research was conducted in Rejo Binangun village of Raman Utara Subdistrict of East Lampung Regency in which data was collected in June 2014.  This research employed a cencus method, involving 34 farmers.  The first aim was analyzed by profit analysis, while the second by risk analysis using standard deviation and coefficient variances.  The third aim was analyzed by product moment of Pearson correlation, whereas the fourth and fifth by descriptive analysis respectively.  The results of this research showed that soybean farming on planting season (MT) 1 until MT 5 had advantages over total cost (R/C>1).  The results of the risk analysis showed that the value of CV<0.5 and of L>0, it meant that soybean farming was still profitable in any level of risk. There was negative correlation between the amount of risk and profit, it meant that higher risk gave lower profit. The sources of risk toward soybean farming were weather and climate, pest and disease attack, land condition, and price.  The farmers made some efforts in addressing risk impact by improving crop pattern, controling pest and disease, liming the land and postponing the crop harvest sale. Key words: farming, risk, soybean